Características del esfuerzo en competición en jugadoras de baloncesto de élite durante las fases finales de la Euroliga y el Campeonato del Mundo - Oliveira-Da-Silva, L.; Sedano-Campo, S.; Redondo-Castán, J. C. (Revista Internacional de Ciencias del Deporte, 2013)
The main aim of the current study was to establish the competitive demands, in terms of external load, of elite female basketball players during the final phase of Euroleague and World Championship. Eight matches corresponding to the play-offs of these competitions were analyzed. A detailed analysis of the movement patterns of 96 players was performed. Eight categories were employed to classify the movements: stand/walk, jog, run, stride/sprint, low shuffle, medium shuffle, high shuffle and jump. Total time in court, live time and percentage of live time over total time were calculated. On the other hand, the frequency and the mean duration of each movement category were also measured. Results illustrate the intermittent nature of female basketball. The majority of time appears to be devoted to activities more aerobic in nature, and only a small percentage of time is spent engaged in high-intensity activity. However, anaerobic capacity seems to be a better predictor of basketball performance. On the other hand, only guards seem to have a specific movement pattern different from that of centers or forwards.